TINJAUAN SEMIOTIK TERHADAP MAKNA SIMBOLIK RELIEF LALITAVISTARA PADA CANDI BOROBUDUR - Sukowati, Ida (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2014)
Borobodur is one of the seven man-made wonders in the world. It suggest the most intringuin questions with regards to symbolic meaning, hence this research attemps to show the symbolic in Borobudur temple, that is the Lalitavistara Relief. On that basis this research using systematic-reflektive approach takes in material from the two mainstream of semiotics, beginning with Charles Sanders-Pierce and then Umberto Wco. Supported by symbols theory with Susanne K. Langer. Tistoric, eshe method used here are historic, descritiv,synthetic-analysis, and critical-reflexsive. The results of this research are; in Lalitavisara relief of there are 314 manifestation of symbol, there are: 88 items Amisa Puja symbol,48 items Mudra symbol, 3 items Trikarya symbol, 2 items Dharmadatu symbol,43 items Anicca-Budha symbol, 126 items are respective symbol, and 4 special symbol.